Method of Light Bulbs Analysis on Vehicles Damaged in Traffic Accidents - Horvat, Rajko; Barišić-Jaman, Berislav; Mršić, Gordan; Špoljarić, Igor; Vrdoljak, Andro; Pehar, Ivan (Promet - Traffic&Transportation, 2012)
One of the measures to increase road traffic safety in Croatia is the introduction of obligatory use of daily lights on vehicles in road traffic during driving, regardless of the visibility and the time of day. The paper describes the new original technical and technological procedure of analysing automotive light bulbs in order to find the traces of glass particles of the broken glass balloon in the marginal cases of action of small inertia forces generated as result of a traffic accident. Investigations of light bulbs in traffic accidents had been rarely done before; therefore the subject of this scientific research is the analysis of the light bulb filament used in automobiles to light the road ahead and to give light signals, i.e. all the light signalling devices on the automobile using the new technical and technological procedure by means of SEM/EDX method. The scientific research has improved the investigation procedure in analysing the light bulbs on automobiles in determining whether at the moment of the traffic accident the regulatory lights were switched on. In determining the responsibility of participants for causing the traffic accident, such a fact may sometimes be of crucial significance. KEY WORDS: traffic accident, light bulb, technical and technological procedure, lights in traffic, microscope, molten glass particles